Contribution of Oxidative Stress to Non-AIDS Events in HIV-Infected Patients. (1st June 2017) - Masiá, Mar; Padilla, Sergio; Fernández, Marta; Barber, Xavier; Moreno, Santiago; Iribarren, José Antonio; Portilla, Joaquín; Peña, Alejandro; Vidal, Francesc; Gutiérrez, Félix
Abstract : Objective: Recognition of potentially modifiable mechanisms implicated in the pathogenesis of non-AIDS events (NAEs) might help improve outcomes of HIV-infected individuals. HIV infection has been associated with increased oxidative stress. We assessed the association between F2-isoprostanes and serious NAEs, and whether they improve the predictive performance of inflammation and coagulation biomarkers. Methods: Prospective multicenter cohort. Individuals who had an incident serious NAE and 2 sex- and age-matched participants with no events were selected. Measurement of F2-isoprostanes, highly sensitive C-reactive protein, interleukin-6, D-dimer, sCD14, sCD40, sCD163, and neopterin levels was performed in successive plasma samples collected from cohort inclusion. Results: Biomarkers were measured in 78 participants developing serious NAEs or death, and 151 subjects with no events. Adjusted levels of F2-isoprostanes, and also of highly sensitive C-reactive protein, sCD14, and D-dimer were higher in individuals who developed serious NAEs, including or not non-AIDS deaths. The same results were observed when only samples collected since the time of achieving virological suppression were analyzed. The additive incorporation of each biomarker, ending with F2-isoprostanes, in an adjusted model was associated with a graded and significant increase in the quality of model fitting, and 94% sensitivity, 33% specificity, and 0.77 accuracy to predict serious NAEs including non-AIDS–related death. Conclusion: Oxidative stress is associated with a higher risk of serious NAEs, including non-AIDS deaths. This effect is independent and additive to biomarkers of inflammation, monocyte activation, and coagulation. Our results suggest that oxidative stress should be included among mechanisms to deal with to improve prognosis of HIV-infected individuals. Abstract : Supplemental Digital Content is Available in the Text.